Environmental contamination in a coronavirus disease 2019 (COVID-19) intensive care unit—what is the risk? - Ong, Sean Wei Xiang (2022)
The risk of environmental contamination by severe acute respiratory coronavirus virus 2 (SARS-CoV-2) in the intensive care unit (ICU) is unclear. We evaluated the extent of environmental contamination in the ICU and correlated this with patient and disease factors, including the impact of different ventilatory modalities.